Diagnostic and prognostic value of serum soluble suppression of tumorigenicity-2 in heart failure with preserved ejection fraction: A systematic review and meta-analysis - Shi, Yujiao; Liu, Jiangang; Liu, Chunqiu; Shuang, Xiong; Yang, Chenguang; Qiao, Wenbo; Dong, Guoju (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure (HF) with preserved ejection fraction (HFpEF) is a growing public health burden, with mortality and rehospitalization rates comparable to HF with reduced ejection fraction (HFrEF). The evidence for the clinical usefulness of soluble suppression of tumorigenicity 2 (sST2) in HFpEF is contradictory. Therefore, we conducted the following systematic review and meta-analysis to assess the diagnostic and prognostic value of serum sST2 in HFpEF. Methods: PubMed and Scopus were searched exhaustively from their inception until March 15, 2022. In diagnostic analysis, we compared the diagnostic value of serum sST2 in HFpEF to NT pro-BNP. We separately pooled the unadjusted and multivariate-adjusted hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) in prognostic analysis. Results: A total of 16 publications from 2008 to 2021 were examined. The results of this analysis were as follow: Firstly, compared with NT pro-BNP, sST2 obtains poor diagnostic performance in independently identifying HFpEF from healthy controls, hypertensive patients, and HFrEF patient. Nevertheless, it may provide incremental value to other biomarkers for diagnosing HFpEF and deserves further investigation. Secondly, log sST2 was independently associated with adverse endpoints on multivariable analysis after adjusting for variables such as age, sex, race, and NYHA class. Per log unit rise in sST2, there was a 2.76-fold increased risk of all-cause death (HR:2.76; 95% CI (1.24, 6.16); p = 0.516, I2 = 0%; P= 0.013) and a 6.52-fold increased risk in the composite endpoint of all-cause death and HF hospitalization (HR:6.52; 95% CI (2.34, 18.19); p = 0.985, I2 = 0%; P=0.000). Finally, the optimal threshold levels of serum sST2 need further determined. Conclusions: Higher sST2 was strongly linked to an increased risk of adverse outcomes in HFpEE. Especially, log sST2 independently predicted all-cause death and the composite endpoint of all-cause death and HF hospitalization. However, prospective and multicenter studies with large-sample and extended follow-up periods are required to validate our results due to limitations in our research.